1992
DOI: 10.1111/j.1745-6584.1992.tb01556.x
|View full text |Cite
|
Sign up to set email alerts
|

Storage Coefficients and Vertical Hydraulic Conductivities in Aquitards Using Extensometer and Hydrograph Data

Abstract: A method is presented to estimate elastic and inelastic specific storage and vertical hydraulic conductivities in aquitards in multilayered flow systems. Borehole extensometer records and ground‐water hydrographs from piezometers are used to construct plots of effective stress and deformation. Elastic and inelastic specific storage are estimated from the plots of effective stress and deformation during loading and unloading cycles. The elapsed loading time is estimated from the same plots and is used to calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…An exact match to InSAR-based estimates would be produced if S s values were individually adjusted by 60-160%, mean of ±20%, maintaining the 1 : 10 sand-clay ratio. This range is consistent with values reported for these sediment types (e.g., Domenico and Mifflin 1965, Cleveland et al 1992, Burbey 2003. Although storage properties undoubtedly vary among well locations, our results are based on uniform values as we have no map of measured S s for this region.…”
Section: Resultssupporting
confidence: 90%
“…An exact match to InSAR-based estimates would be produced if S s values were individually adjusted by 60-160%, mean of ±20%, maintaining the 1 : 10 sand-clay ratio. This range is consistent with values reported for these sediment types (e.g., Domenico and Mifflin 1965, Cleveland et al 1992, Burbey 2003. Although storage properties undoubtedly vary among well locations, our results are based on uniform values as we have no map of measured S s for this region.…”
Section: Resultssupporting
confidence: 90%
“…The loop‐like hysteresis in extensometer records has been observed and analyzed at many locations, from Riley's early work in California to more recent applications in Colorado [ Harmon , 2002]. Cleveland et al [1992] applied this approach to extensometer data from Houston, TX. They demonstrated that hysteresis occurs in these data, and they used the hysteresis loop to identify parameters associated with elastic and inelastic deformation.…”
Section: Discussionmentioning
confidence: 99%
“…In the first group, the initial K v , S ske , and S skv values for the first case are obtained from the joint analytic method. In the second group, the initial K v , S ske , and S skv values for the first case are, respectively, 5.11 × 10 −2 m/year, 1.1 × 10 −4 m −1 and 4.7 × 10 −4 m −1 , which are determined by Ye and Xue () using the stress‐strain diagram method proposed by Cleveland et al (). The initial hminu and hmino values in the underlying and overlying aquifers are set equal to the smallest values of hydraulic heads within the first observational cycle, namely hminu=prefix−5.350.5emnormalm and hmino=prefix−0.040.5emnormalm (Table ).…”
Section: Field Applicationmentioning
confidence: 99%
“…In the first group, the initial K v , S ske , and S skv values for the first case are obtained from the joint analytic method. In the second group, the initial K v , S ske , and S skv values for the first case are, respectively, 5.11 × 10 −2 m/year, 1.1 × 10 −4 m −1 and 4.7 × 10 −4 m −1 , which are determined by using the stress-strain diagram method proposed by Cleveland et al (1992)…”
Section: Inverse Modeling Of Hydraulic Parametersmentioning
confidence: 99%